PENGARUH TEKNIK MEJA BUNDAR TERHADAP HASIL BELAJAR MENULIS TEKS DESKRIPTIF SISWA KELAS VIII MTSN 4 PADANG - Rahma Kurnia Ilahi; Fajrilhuda Yuniko; Fitra Afrida Amna (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to examine the effect of roundtable technique on descriptive text writing. The research design of this technique is quasi-experimental. The experimental group got 80.2 while the control group got 71.08. The results of this research showed that students who learned by using the Roundtable technique produced better descriptive text writing compared to those who learned by using the direct instruction technique. It can be concluded that teaching descriptive text writing by using Roundtable technique gives better results in students' writing than direct instruction. The population was class II students of MTSN 4 Padang. Two classes were randomly selected as research samples. During the treatment, students in the experimental group used the Roundtable technique, while students in the control group used the Direct Instruction Technique. Analysis of the test results showed that the experimental group students' scores were higher than the control group. In the post test, the average score of the experimental group got the best result.